2014
DOI: 10.1371/journal.pgen.1004491
|View full text |Cite
|
Sign up to set email alerts
|

Sox11 Is Required to Maintain Proper Levels of Hedgehog Signaling during Vertebrate Ocular Morphogenesis

Abstract: Ocular coloboma is a sight-threatening malformation caused by failure of the choroid fissure to close during morphogenesis of the eye, and is frequently associated with additional anomalies, including microphthalmia and cataracts. Although Hedgehog signaling is known to play a critical role in choroid fissure closure, genetic regulation of this pathway remains poorly understood. Here, we show that the transcription factor Sox11 is required to maintain specific levels of Hedgehog signaling during ocular develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 77 publications
(106 reference statements)
4
64
1
Order By: Relevance
“…As mentioned previously, we have shown that knockdown of Sox11 causes coloboma due to an elevation of Hh signaling (Pillai-Kastoori et al, 2014). Moreover, the coloboma phenotype in both sox11 and sox4 morphants resembles other animal models of overactive Hh signaling (Lee et al, 2008; Bassett et al, 2010; Lee et al, 2012; Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…As mentioned previously, we have shown that knockdown of Sox11 causes coloboma due to an elevation of Hh signaling (Pillai-Kastoori et al, 2014). Moreover, the coloboma phenotype in both sox11 and sox4 morphants resembles other animal models of overactive Hh signaling (Lee et al, 2008; Bassett et al, 2010; Lee et al, 2012; Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 52%
“…Therefore, we asked whether cyclopamine, a pharmacological Hh inhibitor, could reduce the incidence of coloboma in sox4 morphants. We treated sox4 morphants with 2 μM cyclopamine, a concentration which did not produce any ocular defects on its own (Figure 5E), and which was shown previously to rescue the coloboma phenotype in zebrafish blowout mutants (which carry a mutation in the ptch2 receptor) and sox11 morphants (Lee et al, 2008; Pillai-Kastoori et al, 2014). Sox4 morphants were exposed to either cyclopamine or an equivalent amount of ethanol vehicle from 5.5 to 13 hpf, and then analyzed at 48 hpf for the presence of coloboma.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…These features could be mimicked in surface fish by shh overexpression, and eye development was restored partially in cavefish embryos by using cyclopamine (Yamamoto et al 2004). Recently, it has been demonstrated that mutations in SOX11 and SMAD7 may lead to various ODA through the activation of the SHH pathway (Zhang et al 2013;Pillai-Kastoori et al 2014). In humans, PTCH1 mutations have been associated previously with basal cell nevus syndrome (BCNS) (MIM#109400) and with holoprosencephaly (HPE7) (MIM#610828).…”
Section: Discussionmentioning
confidence: 99%